Total carotenoid degradability in alfalfa (Medicago sativa L) in an in vitro culture with ruminal liquid - Vera-Vázquez, Francisco J.; López-Garrido, Serafín; Guerrero-Legarreta, Isabel; Mota-Rojas, Daniel; Bautista-Martínez, Yuridia; Cruz-Monterrosa, Rosy (Ecosistemas y Recursos Agropecuarios, 2022)
The objective of the work was to  evaluate the degradability of dry matter (DM) and that of carotenes of alfalfa (Medicago sativa L) in an in vitro study. The samples were incubated at 39 ◦ C at 0, 12, 24, 48 and 72 h. The data were processed with an analysis of variance, Tukey’s test (p < 0.05). The results of the alfalfa analysis were: DM = 24.42, MO = 96.79, PC = 21.22, FDA = 29.11, NDF = 36.24, ash = 3.21 and total carotenes = 254.6 mg g−1. 43% of DM disappeared at 12 h (P < 0.001), while from 12 to 72 h, the DM reached a degradation of 62% (P < 0.001). The degradation of alfalfa carotenes is associated with the rate of DM degradation, the study allowed to obtain a simulation of the bovine rumen indicating that most of the carotenes disappear in less than 12 h of incubation.